Residential mobility, second homes and quality of life: Consequences of moving out from the city of Madrid - Lardiés-Bosque Raúl (Bulletin of Geography. Socio-Economic Series, 2017)
Residential mobility and migration of retired people is an emerging issue in western societies. Moreover, the Quality of Life (QoL) of old people has become a challenge in our societies, of great interest for researchers and planners. Nevertheless, few studies have investigated how mobility and/or migration help improve QoL. This paper aims to determine the influence of retired people’s residential mobility on the different dimensions of their life. Factors driving residential mobility in this population group are analysed, as well as the sociodemographic characteristics of this group, family, friends and social contacts, and environmental conditions, before and after moving. The methodology used is qualitative and the results have been obtained from 29 in-depth interviews with aged people who have moved from the city of Madrid to other places in Spain. The consequences of the moves are analysed in terms of how the different dimensions of their QoL and their well-being are affected.